Governor of East Kalimantan Political Leadership Opinion in Responding to Covid-19 Policies - Iman Surya; Sanny Nofrima; Niken Nurmiyati; Herdin Arie Saputra (Nyimak: Journal of Communication, 2021)
This study aims to develop an understanding of opinion leadership in improving communication about digital media to encourage deeper engagement and share information on various digital platforms in identifying opinion leadership. Novelty in this study is the response to the opinion leaders of the East Kalimantan Governor’s political discourse in the Covid-19 response policy. This research uses qualitative research. Data was collected using primary data in the form of in-depth interviews with the people of East Kalimantan and supported by secondary data in the form of fifteen online media and the official website of the East Kalimantan government. Data analysis using Nvivo 12 Plus software to get more professional results. The results of this study are that the Covid-19 management policy received positive and negative responses from the people of East Kalimantan, each showing a figure of 21.43 per cent and 78.57 per cent. This study concludes that there is no harmony between the opinions of political leadership in the media and the implementation of existing policies in the community. The opinion of the leadership of the Governor of East Kalimantan can play a central role in disseminating broad and fascinating ideas based on ideas classified into five different types, each based on knowledge, education, expertise, innovation, media presence.Keywords: Covid-19, east Kalimantan, policy, opinion leadership, response ABSTRAKPenelitian ini bertujuan untuk mengembangkan pemahaman tentang kepemimpinan opini dalam meningkatkan komunikasi tentang media digital sehingga mendorong keterlibatan yang lebih dalam, untuk berbagi informasi di berbagai platform digital dalam identifikasi kepemimpinan opini. Novelty dalam penelitian ini yaitu respon kepemimpinan opini wacana politik Gubernur Kalimantan Timur dalam kebijakan penanggulangan Covid-19. Penelitian ini menggunakan penelitian kualitatif. Pengumpulan data dilakukan dengan menggunakan data primer berupa wawancara-mendalam (in-depth interview) dengan masyarakat Kalimantan Timur. Didukung oleh data sekunder berupa lima belas media online dan web resmi pemerintah Kalimantan Timur. Analisis data menggunakan software Nvivo 12 Plus, agar mendapatkan hasil yang lebih profesional. Hasil penelitian ini yaitu dalam kebijakan pengelolaan Covid-19 mendapatkan respon positif dan negatif dari masyarakat Kalimantan Timur, masing-masing menunjukkan angka sebesar 21,43 persen, dan 78,57 persen. Kesimpulan dari penelitian ini yaitu belum ada keselarasan antara opini kepemimpinan politik dalam media dengan implementasi kebijakan yang ada di tengah masyarakat. Opini kepemimpinan Gubernur Kalimantan Timur dapat berperan sentral dalam penyebaran ide yang luas, dan sangat menarik berdasarkan gagasan yang telah diklasifikasikan dalam lima jenis yang berbeda, masing-masing berdasarkan pengetahuan, edukasi, keahlian, inovasi, kehadiran dalam media. Kata Kunci: Covid-19, Kalimantan Timur, kebijakan, opini kepemimpinan, respon